Ceramic Materials for Energy Applications : Ceramic Engineering and Science Proceedings. - Lin, Hua-Tay (Ceramic Engineering and Science Proceedings Ser., 2011)
This book is a collection of papers from The American Ceramic Society's 35th International Conference on Advanced Ceramics and Composites, held in Daytona Beach, Florida, January 23-28, 2011. This issue includes papers presented in the Ceramics for Electric Energy Generation, Storage and Distribution; Advanced Ceramics and Composites for Nuclear and Fusion Applications; and Advanced Materials and Technologies for Rechargeable Batteries symposia.